Coleta, utilização indevida e proteção de dados no ambiente digital na legislação brasileira: a internet das coisas como sistema de transferência de dados pessoais - Cruz, Eduardo Otaciano da (2024)
The Information Society is characterized by the rapid evolution and dissemination of information and communication technologies. Beyond the Internet, the growing spread of the Internet of Things (IoT) stands out, an emerging technology that connects physical devices, systems, and objects, generating a vast amount of data. When adequately processed, this data transforms into valuable information. IoT has a significant impact on all sectors of the economy and society, having rapidly evolved in recent years. By connecting various smart devices, IoT generates and stores vast amounts of data, which enhance efficiency, safety, and quality of life. Additionally, Artificial Intelligence (AI) associated with the Internet of Things allows the collected data, converted into information, to be processed in an advanced manner, enabling professionals to make immediate and well-founded decisions. This results in more objective and informed choices, based on detailed reports. Furthermore, AI, by using personal data collected in digital environments, can anticipate the individual behavior of certain people, influencing decisions that impact their lives. This encompasses everything from commercial transactions to interactions with the state, directly affecting access to goods, services, and job market opportunities. In this scenario, however, various legal issues related to the privacy and security of data stored in the digital environment emerge: the handling of data arising from innovations in digital environments can constitute a considerable risk to privacy and the protection of personal data. Thus, the general objective of this dissertation is to explore the challenges related to privacy and data protection arising from Information and Communication Technologies, focusing on the Internet of Things, considering the risks associated with the collection, processing, and misuse of personal information. To this end, it initially discusses the Information Society and how the Internet of Things has raised new legal assets to be protected. Next, it presents the Brazilian regulatory framework on data protection and privacy in digital environments, with special attention to the General Data Protection Law. Finally, it discusses the vulnerabilities and risks associated with inadequate protection of personal data in digital environments. The research employs an exploratory-descriptive methodology and a qualitative approach, as well as employs bibliographic and documentary procedures. It concludes that the protection of personal data in the digital environment, specifically in the context of the Internet of Things, requires a multifaceted approach involving technological advances, effective legal regulations, responsible business practices, and informed digital citizenship. Only through combined efforts at all these levels can it be ensured that privacy and security of personal data are fully respected and protected in the digital age.